2014
DOI: 10.5530/pj.2014.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of a polyherbal formulation (HC9) and comparative analysis of its cytotoxic activity with the individual herbs present in the composition in breast cancer cell lines

Abstract: Introduction: The present study aims to standardize a polyherbal formulation (HC9) that was previously shown to exhibit excellent antioxidant and cytotoxic activity in breast cancer cells. Here, we have compared the cytotoxic activity of HC9 with its individual components in breast cancer and non-cancerous cells. Methods: Physico-chemical and phytochemical evaluation of HC9 was performed. Qualitative and quantitative HPTLC analysis of component herbs and HC9 was done by using specific markers. The cytotoxic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The kidneys excrete metabolic waste products and regulate the serum concentration of a variety of substances (Benouadah , 2016). Creatinine is an important biomarker of renal toxicity and increases the levels of these parameters indicates a marked renal damage (Suryavanshi , 2015). Results from this study showed that oral administration of hexane extract to albino rats revealed the insignif icant changes of most of the serum biochemical parameters which suggest the nontoxic nature of the extract.…”
Section: Discussionmentioning
confidence: 67%
“…The kidneys excrete metabolic waste products and regulate the serum concentration of a variety of substances (Benouadah , 2016). Creatinine is an important biomarker of renal toxicity and increases the levels of these parameters indicates a marked renal damage (Suryavanshi , 2015). Results from this study showed that oral administration of hexane extract to albino rats revealed the insignif icant changes of most of the serum biochemical parameters which suggest the nontoxic nature of the extract.…”
Section: Discussionmentioning
confidence: 67%
“…Pterocarpus santalinus (Azamthulla et al, 2015) has shown hepatoprotective activity, and M. azedarach (Ervina & Sukardiman, 2018) showed activity against different cancer cell lines. Previously, we have reported the anticancer activity of polyherbal formulations, Panchvalkal (Aphale et al, 2018) and HC9 (Suryavanshi et al, 2014) against cervical cancer and breast cancer, respectively. LCMS analysis revealed that alkaloids were the major phytochemicals present in HMK, along with flavonols, stilbenes, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the polyherbal formulations exhibit anticancer activity by decreasing the viability and growth rate of cancer cells. In some of the studies conducted by our research group, polyherbal formulations such as Panchvalakala (Aphale et al, 2018(Aphale et al, , 2021 and HC9 (Suryavanshi et al, 2014) exhibited anticancer activity against cervical cancer and breast cancer cells, respectively, by decreasing their viability and growth kinetics. The results of the current investigation showed that HMKaq not only had anti-proliferative capability but also displayed safety towards non-cancerous cells.…”
Section: Discussionmentioning
confidence: 99%